2016
DOI: 10.1159/000431224
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Admissions to the Intensive Care Unit in a Tertiary Hospital

Abstract: Aims: A better understanding of the characteristics of obstetric patients admitted to an intensive care unit (ICU) could guide where the focus of obstetric training and awareness should be directed at to reduce further maternal mortality and morbidity. Methods: We retrospectively assessed the charts of all women admitted during pregnancy or postpartum to a tertiary ICU over a 12-year period. We retrieved whether women were followed locally or referred from another hospital and whether the ICU admission was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
4
7
1
Order By: Relevance
“…These results are comparable to those obtained in other countries. 5,8,9 The majority of women admitted to ICU were postpartum (90%), which is in accordance with the published literature. 5,[8][9][10][11] The length of ICU stay in present study, 5 days (IQR, 1 -66 days), was comparable with most of the published studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are comparable to those obtained in other countries. 5,8,9 The majority of women admitted to ICU were postpartum (90%), which is in accordance with the published literature. 5,[8][9][10][11] The length of ICU stay in present study, 5 days (IQR, 1 -66 days), was comparable with most of the published studies.…”
Section: Discussionsupporting
confidence: 89%
“…5,8,9 The majority of women admitted to ICU were postpartum (90%), which is in accordance with the published literature. 5,[8][9][10][11] The length of ICU stay in present study, 5 days (IQR, 1 -66 days), was comparable with most of the published studies. 5 The most common reasons for ICU admission in this study were hypertensive disorders of pregnancy in 35.5% and obstetric haemorrhage in 24.7%, sepsis/infection in 20.4%, non-obstetric diagnoses in 13% and other obstetric complications in 6.4%.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, cardiac disorder was the most common reason for non-obstetric causes of ICU admission, in contrast with the findings of other studies in which sepsis was reported to be the predominant non-obstetric reason for ICU admission [8,10,11]. In Belgium, however, pre-existing and acquired cardiopathies were the most common cause for ICU admission and surpassed hypertensive disorders and hemorrhage [12]. In our hospital, the cardiac critical care unit (CCU) is a relatively independent intensive care unit, and this study did not include critically ill obstetric women in the CCU.…”
Section: Discussioncontrasting
confidence: 98%
“…(25) This difference might be due to socioeconomic conditions, the quality of prenatal care, or better modalities of treatment in the ICU. (26) …”
Section: Discussionmentioning
confidence: 99%